Hyperréalistes Américains : Richard Artschwager - Robert Bechtle - Charles Bell - John Clem Clarke - Robert Cottingham - Richard Estes - Audrey Flack - Ralph Goings - John Kacere - Richard Mc Lean - Noël Mahaffey - Malcolm Morley - John Salt - Paul Sarkisian - Stephen Posen. - Hogan, Carroll Edward (Paris : Galerie Arditti, 1973)
Artschwager, Richard ; Bechtle, Robert ; Bell, Charles ; Clarke, John Clem ; Cottingham, Robert ; Estes, Richard ; Flack, Audrey ; Goings, Ralph ; Kacere, John ; McLean, Richard ; Mahaffey, Noël ; Morley, Malcolm ; Salt, John ; Sarkisian, Paul ; Posen, Stephen
Engels
boek
Keywords: Amerika